Determinants of financial distress in Nigerian deposit money banks: A panel modelling approach - OKERE, Wisdom; AMBE, Cosmas (Asian Journal of Economic Modelling, 2025)
This study examines the determinants of financial distress of listed deposit money banks (DMBs) in Nigeria from 2010 to 2022. Founded on the financial ratio theory and integrating behavioral managerial traits within the framework, the research employs a quantitative approach, using panel data from eight publicly listed DMBs and applying the panel ordinary least squares regression (Panel OLS) and robust standard errors and Fully Modified Ordinary Least Squares (FMOLS) to capture long-run dynamics. Findings reveal that capital adequacy, exchange rate, and inflation rate significantly increase the likelihood of financial distress, while bank size significantly reduces financial distress due to economies of scale. The FMOLS estimates corroborate the significance of exchange rate and inflation rates while highlighting asset quality and deposit structure as key long-term determinants. GDP and liquidity ratio remain insignificant, and managerial overconfidence exerts no significant impact. The findings pinpoint that macroeconomic and firm-specific factors drive financial distress in DMBs. Therefore, policymakers are advised to strengthen capital regulation, enforce thorough asset quality controls, and implement macroeconomic policies that support growth in the financial sector. This research contributes to the body of knowledge on financial stability in Sub-Saharan Africa, offering insights for mitigating distress in emerging financial markets.